Development of Dr. Zhulfi Clinic Website-Based Service Management System - Misbaqhul Diky Kurniawan; Zulfikar Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Dr. Zhulfi's clinic currently faces various challenges in managing patient services, such as long waiting times, difficulty in accessing medical records, and inefficient appointment arrangements. This study aims to develop a website-based clinic management system that can optimize patient services by increasing the effectiveness and efficiency of clinic operations. The research methodology includes data collection through observation, interviews, and surveys to clinic staff and patients to identify existing needs and problems. Based on the results of the needs analysis, a prototype system was designed that includes key features such as online registration, electronic medical record management, appointment setting, and automatic reminder system. The system was developed using modern web technologies and thoroughly tested to ensure its reliability and ease of use. Initial implementation was conducted in one clinic department, followed by user training and system performance evaluation. The evaluation results showed significant improvements in service efficiency, with shorter patient waiting times and faster and more accurate data access. This study concludes that a web-based clinic management system can provide an effective solution to address operational issues at Dr. Zhulfi's Clinic, as well as improve overall patient satisfaction. Recommendations for further development include integration with the clinic's financial and inventory management systems.